The Contact Between Dialects of Mid - Kirmanji Accent in Koya City - حه‌مه‌د ده‌ریا; Sabir, Shadan (Humanities Journal of University of Zakho, 2020)
The title of this research is (the contact between dialects of mid - Kirmanji accent in Koya City). The reason behind selecting this research is that this subject and the title are new; there are few researches on this topic. In this research, we want to explain this linguistic phenomenon; the purpose is to explain these contacts that takes place between the dialect of Koya City and other mid - Kirmanji dialects. This linguistic phenomenon is apparent in Koya due to the geographical location of the city. Our research method is analytical and descriptive. The martials of our research are words, expressions and sentences spoken by people in the research area. The content of this research comprises of an introduction and three parts. In the first part, we talk about language, dialect, concepts and definition of dialect, Kurdish accents, the concepts, definitions and the types of contact. The second part is about the reason we chose Koya as an example. Also, we clarify the reason led to the contact between the dialects in the research area. In the third part, we give examples practically and present the contact of the dialects within the context of these examples, in the fields of syntax, phonology, morphology and dictionary. This research ends with conclusions and the list of references.